The "Ownership" of Churches: Ethnic, Racial, and Language Groups in U.S. Catholicism - Hoover, Brett (Eurostudia, 2017)
Traditional understandings of ownership emphasize legal or economic property rights, but these conceptions come up short when examining faith communities in the United States context, where congregants often feel and act as “owners,” regardless of legal property rights. International migration to the United States further complicates this “felt ownership” within faith communities, as distinct racial, ethnic, or language groups compete or cooperate around their claims of ownership. In those Roman Catholic faith communities known as “shared parishes,” where multiple racial, ethnic, or language groups have separate worship and ministries but share facilities and leadership (Hoover 2014), the complex negotiations of sharing demonstrate the power dynamics between groups. A two-year case study of three such parishes in the Los Angeles area shows how the “felt ownership” of particular groups is privileged or limited by the various factors that shape the often asymmetrical power dynamics between the groups in U.S. society.